Penerapan Edukasi Minum Obat pada Pasien Gangguan Persepsi Sensori: Halusinasi Pendengaran: Medication Education Strategies for Patients Experiencing Auditory Hallucinations - Vernanda Arya Pratama; Ana Puji Astuti (Jurnal Keperawatan Berbudaya Sehat, 2026)
Patients with sensory perception disorders auditory hallucination were managed with drug therapy to control hallucinations using education of five right medication, providing an explanation of the side effects of not taking medication and how to get medication. The implementation of pharmacological management is expected to enable patients to control their hallucinations. The goal of this study is describing patient control their hallucinations by education of taking medication correctly. This study used descriptive method with nursing process approach which describes the entire process of managing sensory perception disorders: hallucinations with an understanding of the 5 rights medication. Data collected for three days to a patient with auditory hallucination in condemning phase. The implementation of education about the importance of medication, the risks if not taken, and the side effects of medication. The result showed the patients looks calmer, consume medication independently and can control their hallucinations, and continue treatment until there is a medical decision regarding stopping or adjusting the dose. Compliance in taking medication for successful recovery is important thing should be aware by patient and family.